2020
DOI: 10.1088/1748-605x/ab99d6
|View full text |Cite
|
Sign up to set email alerts
|

A printing-spray-transfer process for attaching biocompatible and antibacterial coatings to the surfaces of patient-specific silicone stents

Abstract: An antibacterial coating with stable antibacterial properties and favorable biocompatibility is recognized as an effective method to prevent bacterial adhesion and biofilm formation on biomedical implant surfaces. In this study, a convenient and low-cost printing-spray-transfer process was proposed that enables reliably attaching antibacterial and biocompatible coatings to patient-specific silicone implant surfaces. A desktop three-dimensional printer was used to print the mold of silicone implant molds accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Bacteriostasis is another significant property for the implant, so many studies have also explored the surface structures with antibacterial properties [9][10][11]. Inspired by the antimicrobial attachment performance of lotus leaf, Cheng et al [12] investigated the micro/nanoscale roughness effects on surface wetting by intentionally altering the lotus leave structures while keeping the chemical composition approximately the same, results showed that the combination of the microscale mounds and the nano-scale hair-like structures caused the antiadhesion and self-cleaning ability.…”
Section: Introductionmentioning
confidence: 99%
“…Bacteriostasis is another significant property for the implant, so many studies have also explored the surface structures with antibacterial properties [9][10][11]. Inspired by the antimicrobial attachment performance of lotus leaf, Cheng et al [12] investigated the micro/nanoscale roughness effects on surface wetting by intentionally altering the lotus leave structures while keeping the chemical composition approximately the same, results showed that the combination of the microscale mounds and the nano-scale hair-like structures caused the antiadhesion and self-cleaning ability.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of violet-blue light treatment and photosensitisers for surface decontamination has the potential for wide use in healthcare applications. The biocompatibility and stability of TiO 2 allows for its incorporation into a range of polymeric materials for medical devices, including commonly used elastomers [22,23] such as polydimethylsiloxane (PDMS). It can be incorporated into materials by a range of different methods [17] that either result in surface coating or bulk doping.…”
Section: Introductionmentioning
confidence: 99%